2004
DOI: 10.1080/14992020400050073
|View full text |Cite
|
Sign up to set email alerts
|

Social hearing measured with the Performance Inventory for Profound and Severe Loss: a comparison between adult multichannel cochlear implant patients and users of acoustical hearing aids

Abstract: The objective of this study was to investigate social hearing in successful users of multichannel cochlear implants (CIs) and to compare the scores with those of a group of hearing-impaired adults using acoustical hearing aids (HAs). Out of 88 patients who had undergone surgery, 75 CI users with a mean age of 55 years and a mean pre-operative hearing level of 113dB in the better ear were compared with 59 users of acoustical HAs with a mean age of 56 years and a mean hearing level of 82dB in the better ear. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…It may be observed, therefore, that profound hearing loss was not a limiting aspect in obtaining the results in hearing and spoken language. These findings corroborate the study which states that the use of the cochlear implant can allow access to speech sounds for profound hearingimpaired children 33 .…”
Section: Discussionsupporting
confidence: 81%
“…It may be observed, therefore, that profound hearing loss was not a limiting aspect in obtaining the results in hearing and spoken language. These findings corroborate the study which states that the use of the cochlear implant can allow access to speech sounds for profound hearingimpaired children 33 .…”
Section: Discussionsupporting
confidence: 81%
“…[10][11][12][13][14] Moreover, unilateral cochlear implantation has resulted in an improvement in quality of life after implantation for all cochlear implant (CI) users, both young and old. [15][16][17][18][19][20][21][22][23][24] However, their ability to understand speech in noisy environments and to localize sounds remains poor. This reduced speech recognition in noise is a significant problem, especially for young children who attend mainstream schools, in which the level of noise in a classroom may range from 34 to 73 dBA.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven out of the 2,169 papers searched were found to be pertinent to the topic and were rated B for evidence strength (four were rated 2b 1,7-9 and seven 2c [2][3][4][5][6]10,11 ). No Arated publications were found.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that cochlear implants allow for improvements in speech understanding and on qualityof-life, aside from significantly easing one's insertion into the social and professional worlds and reducing the onset of depression and feelings of loneliness 1,3,4,[6][7][8]10 . Shorter hearing deprivation time has been singled out as a factor connected to better outcomes 4,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation